Extratumoral PD-1 blockade does not perpetuate obesity-associated inflammation in esophageal adenocarcinoma. (1st April 2018) - Galvin, Karen C.; Conroy, Melissa J.; Doyle, Suzanne L.; Dunne, Margaret R.; Fahey, Ronan; Foley, Emma; O'Sullivan, Katie E.; Doherty, Derek G.; Geoghegan, Justin G.; Ravi, Narayanasamy; O'Farrelly, Cliona; Reynolds, John V.; et al.
Abstract: Checkpoint inhibitors, such as anti-PD-1 (Programmed death-1), are transforming cancer treatment for inoperable or advanced disease. As the incidence of obesity-associated malignancies, including esophageal adenocarcinoma (EAC) continues to increase and treatment with checkpoint inhibitors are being FDA approved for a broader range of cancers, it is important to assess how anti-PD-1 treatment might exacerbate pre-existing inflammatory processes at other sites. Outside the EAC tumor, the omentum and liver were found to be enriched with substantial populations of PD-1 expressing T cells. Treatment of omental and hepatic T cells with anti-PD-1 (clone EH12.2H7) did not enhance inflammatory cytokine expression or proliferation, but transiently increased CD107a expression by CD8 + T cells. Importantly, PD-1-expressing T cells are significantly lower in EAC tumor post neoadjuvant chemoradiotherapy, suggesting that combination with specific conventional treatments may severely impair the efficacy of anti-PD-1 immunotherapy. This study provides evidence that systemically administered anti-PD-1 treatment is unlikely to exacerbate pre-existing T cell-mediated inflammation outside the tumor in obesity-associated cancers, such as EAC. Furthermore, our data suggests that studies are required to identify the negative impact of concomitant therapies on PD-1 expression in order to boost overall response rates. Highlights: PD-1 + T cells are enriched in the omentum, liver and tumor of EAC patients. Anti-PD-1 does not enhance T cell mediated inflammation in omentum or liver. Blocking PD-1 temporarily restores CD8 + T cell cytotoxic potential. Intratumoral PD-1 expression is significantly reduced following chemoradiotherapy.